Seasonality in the trophic basis of a temperate stream invertebrate assemblage: Importance of temperature and food quality. (24th March 2014) - Junker, James R.; Cross, Wyatt F.
Abstract : Ecologists have long recognized that ecosystems are open and that they receive substantial subsidies of energy and materials from beyond their boundaries. This recognition has spurred theoretical and empirical investigation of biotic and abiotic conditions that influence the importance of subsidies for recipient ecosystems. We combined temporal patterns of resource use (via stable isotope analysis), consumer—resource stoichiometry, and invertebrate production to quantify controls on the relative importance of resource subsidies (i.e., terrestrial litter) vs. in situ food resources (i.e., algae) in fueling secondary production in a highly seasonal temperate stream. Both litter subsidies and in situ primary production were important for supporting annual invertebrate production. However, temporal patterns of secondary production and trophic support varied significantly. Algae supported the majority of production (> 55%) during critical growth periods characterized by warm temperatures (5–15°C) and high primary production. In contrast, terrestrial litter supported the majority of invertebrate production (> 55%) during relatively cold months (µ 0–4°C) when primary production and metabolic demands of invertebrates were low. A model selection procedure revealed that both temperature and consumer—resource stoichiometric imbalances were important determinants of patterns of invertebrate production. Our findings highlight the important interaction of environmental conditions and resource quality in mediating how internally and externally derived resources are used to fuel invertebrate production.